Animal Source Food Intake and Growth Outcomes in Children Aged 6–59 Months: An Ecological Analysis from the Global Dietary Database. (29th May 2020) - Miller, Victoria; Webb, Patrick; Cudhea, Frederick; Zhang, Jianyi; Shi, Peilin; Reedy, Julia; Puklin, Leah; Coates, Jennifer; Micha, Renata; Mozaffarian, Dariush
Abstract: Objectives: The relationship between animal source foods (ASF) and growth outcomes is not well characterized, largely due to few studies and inconsistencies across study designs. We investigated the associations between mean ASF intake, and under-5 mortality and disability-adjusted life years (DALYs) linked to stunting, wasting, underweight and overweight/obesity in children aged 6–59 months. Methods: Intakes of ASF (unprocessed red meat, processed meat, fish, eggs, milk, yogurt and cheese), adjusted to 1000 kcal/day, were estimated using individual-level intake data from nationally and sub-nationally representative diet surveys in the Global Dietary Database. Bayesian hierarchical modeling methods were used to estimate mean intake and its statistical uncertainty for 185 country-, and sex-specific strata. Under-5 mortality and disease specific DALYs data were obtained from the World Bank's World Development Indicators and the Global Burden of Diseases study, respectively. We assessed country- and sex-stratum level cross-sectional associations between ASF and mortality and DALYs using Poisson regression models, adjusting for individual and national-level confounders (sex, dietary intake, education, urbanicity, unemployment rate, poverty rate, income, and geographic region). Results: In 2015, each 1 serving increase in total ASF intake was inversely associated with DALYs linked to under-5 mortality (odds ratio [OR] 0.71, 95% CI 0.65–0.77, P -value < 0.001), stunting (0.89, 0.88–0.91, P -value < 0.001), wasting (0.81, 0.80–0.81, P -value < 0.001), and overweight/obesity (0.86, 0.79–0.93, P -value < 0.001). A positive association with underweight 1.05, 1.04–1.06, P -value < 0.001) was observed. Associations varied by geographic region, for example, higher ASF intake was most beneficially associated with under-5 mortality in Sub-Saharan Africa. Findings by geographic and economic regions and for the individual ASF will be presented at the meeting. Conclusions: Higher ASF intake was associated with a lower risk of under-5 mortality, and DALYs linked to stunting, wasting, and overweight/obesity among children aged 6–59 months. Given the cross-sectional nature, more studies are needed to examine whether the different associations by region are due to biology or confounding factors. Funding Sources: Gates Foundation.